Idiopathic Alopecia—A Retrospective Descriptive Study Integrated with the Current Literature - Andrei Marin; Sabina-Eliza Băloi; Silviu Adrian Marinescu; Adrian Vasile Dumitru; Dana Antonia Țăpoi; Ana Maria Ciongariu; Mircea-Ștefan Tampa; Maria-Roxana Caunic; Dragoș Șerban; Carmen Giuglea (Cosmetics)
Hair loss is a widespread issue affecting both men and women, with significant aesthetic and psychological impacts. This study aimed to evaluate various hair restoration treatments, assess patient satisfaction, and identify the correlations between treatment types, treatment duration, and outcomes. We conducted a retrospective observational study on 50 patients who completed a 26-question online survey about their hair loss experience, treatments tried, and satisfaction levels. The treatments included FDA-approved drugs (finasteride and minoxidil), platelet-rich plasma (PRP) therapy, hormonal treatments, hair transplant surgery, and nutritional supplements. The results showed that a combination of PRP and topical minoxidil/finasteride produced significant improvements in hair density and thickness. Higher patient satisfaction was correlated with multiple treatment combinations and a longer treatment duration, while surgical hair transplants achieved the highest satisfaction rates despite their invasiveness. This study found that consistency and combination treatments are the key to the optimal hair restoration outcomes. Its limitations included a lack of racial diversity among the participants and the reliance on self-reported data. Overall, non-surgical therapies, particularly when combined, offer effective solutions for early-stage hair loss, while hair transplants remain the most definitive option for severe cases.